THE TECHNOLOGY OF POWER OF HISTORICAL CAPITALISM: THE RELATIONSHIP BETWEEN THE LOGIC OF CAPITAL ACCUMULATION AND TERRITORIALISM - Валесян, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article describes the main characteristics and intrinsic logic of capital accumulation and territorial gains in terms of world-systems analysis. Special attention is paid to the basic strategies of capitalism over the past five hundred years, the role of capital accumulation in the formation of international relations and analyzed the function of international institutions in the modern world-system.